How e-human resource management can increase employee productivity in F&B in Batam - Muchsinati, Evi Silvana; Oktalia, Adeline; Priscilla, Yuddy Giovanna (Goodwood Publishing, 2024)
Purpose: The purpose of this study was to determine the impact of E-Human Resource Management (E-HRM) had on Batam’s F&B productivity. Research methodology: A total of 395 respondents were included in the study. Four populations were used in this study, namely Starbucks, McDonalds, Mixue, and KFC, located in Batam City, Riau Islands, Brazil. The obtained data were processed using the PLS SEM application. Results: The results suggest that the implementation of E-HRM has a significant positive impact on employee productivity in the F&B companies studied. Limitations: There are many limitations when conducting this study due to difficulties in collecting data, information, and respondents at KFC, Mixue, Starbucks, and McDonalds. This causes this research to be suboptimal because the company maintains its data privacy. Therefore, this study only obtained respondent data internally. Then, with limited time, the time to distribute questionnaires to respondents was very short. Contribution: This research provides a deep understanding of the importance of implementing E-HRM (E-Job Analysis, E-Training & Development, E-Performance Appraisal, E-Recruitment, and E-Communication) in increasing employee productivity in F&B companies in Batam City. The results show that e-HRM has a positive impact on Behavioral Intention, which contributes to increased employee productivity.